2008
DOI: 10.1016/j.neuroscience.2007.09.084
|View full text |Cite
|
Sign up to set email alerts
|

Impaired nerve regeneration and enhanced neuroinflammatory response in mice lacking pituitary adenylyl cyclase activating peptide

Abstract: Peripheral nerve injury models are used to investigate processes that can potentially be exploited in CNS injury. A consistent change that occurs in injured peripheral neurons is an induction in expression of pituitary adenylyl cyclase activating peptide (PACAP), a neuropeptide with putative neuroprotective and neuritogenic actions. PACAP-deficient mice were used here to investigate actions of endogenous PACAP after facial nerve injury. Although motor neuron survival after axotomy was not significantly differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 43 publications
3
89
0
Order By: Relevance
“…Thus our data clearly demonstrate a functional role of GIP/GIPR signalling in nerve regeneration. Interestingly, very recently it was shown that also the cognate peptide PACAP is critically involved in proper nerve regeneration by controlling lesion-induced immune responses (Armstrong et al, 2008).…”
Section: Impaired Spontaneous Nerve Regeneration In Mice Lacking Giprmentioning
confidence: 99%
“…Thus our data clearly demonstrate a functional role of GIP/GIPR signalling in nerve regeneration. Interestingly, very recently it was shown that also the cognate peptide PACAP is critically involved in proper nerve regeneration by controlling lesion-induced immune responses (Armstrong et al, 2008).…”
Section: Impaired Spontaneous Nerve Regeneration In Mice Lacking Giprmentioning
confidence: 99%
“…Numerous results indicate that it exerts growth factor-like activities in the brain during development, regeneration, and tumorigenesis (6)(7)(8)(9)(10). Indeed, considerable data indicate that PACAP, mainly via PAC1, regulates neural cell proliferation, survival, axon regeneration and oligodendrocyte progenitor proliferation and maturation (6)(7)(8)(9)(11)(12)(13).…”
mentioning
confidence: 99%
“…PACAP is thought to be an important sensory neuropeptide, which was described in the superficial spinal horn layers and in neurons of the dorsal root ganglia (17,22) and can play a role in conduction of sensory stimuli in pain reactions during various pathological processes (15). On the other hand, it is well known that IBD may lead to severe and longlasting pain (3,27).…”
Section: Discussionmentioning
confidence: 99%